2018
DOI: 10.1038/s41598-018-34072-9
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Imaging Markers for Prediction of Radiotherapy Response in Patients with Nasopharyngeal Carcinoma: RESOLVE DWI versus DKI

Abstract: In this prospective study, we compared the performance of readout segmentation of long variable echo trains of diffusion-weighted imaging (RESOLVE DWI) and diffusion kurtosis imaging (DKI) for the prediction of radiotherapy response in patients with nasopharyngeal carcinoma (NPC). Forty-one patients with NPC were evaluated. All patients underwent conventional MRI, RESOLVE DWI and DKI, before and after radiotherapy. All patients underwent conventional MRI every 3 months until 1 year after radiotherapy. The pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 29 publications
0
9
0
Order By: Relevance
“…After screening the titles and abstracts, 22 articles were considered potentially eligible after excluding 108 articles for the following reasons: non-English articles (n = 22), case reports (n = 9), not in the field of interest (n = 56), non-original articles (i.e., reviews, letters, editorials, conference abstracts) (n = 18), and non-human studies (n = 3). After full-text review, nine articles were further excluded because they were not in the field of interest (n = 1) 28 , had overlapping study populations (n = 2) 10 , 29 , had insufficient information for the reconstruction of 2 × 2 tables (n = 1) 30 , insufficient detail of pretreatment ADC (n = 3) 31 33 , or region of interest was on lymph nodes only (n = 2) 34 , 35 . Thirteen original studies were included for qualitative synthesis 5 , 6 , 8 , 9 , 11 19 .…”
Section: Resultsmentioning
confidence: 99%
“…After screening the titles and abstracts, 22 articles were considered potentially eligible after excluding 108 articles for the following reasons: non-English articles (n = 22), case reports (n = 9), not in the field of interest (n = 56), non-original articles (i.e., reviews, letters, editorials, conference abstracts) (n = 18), and non-human studies (n = 3). After full-text review, nine articles were further excluded because they were not in the field of interest (n = 1) 28 , had overlapping study populations (n = 2) 10 , 29 , had insufficient information for the reconstruction of 2 × 2 tables (n = 1) 30 , insufficient detail of pretreatment ADC (n = 3) 31 33 , or region of interest was on lymph nodes only (n = 2) 34 , 35 . Thirteen original studies were included for qualitative synthesis 5 , 6 , 8 , 9 , 11 19 .…”
Section: Resultsmentioning
confidence: 99%
“…However, since SS-EPI is susceptible to magnetic susceptibility artifacts, its image quality has not always been satisfying (9). Furthermore, few studies (22,23) have reported the application of RESOLVE-DWI for nasopharynx tumors, as well as the discrimination of NPL and NPC. In the present study, the ADC maps used for the histogram analysis were obtained using the RESOLVE sequence.…”
Section: Discussionmentioning
confidence: 99%
“…DKI-derived kurtosis and diffusion metrics are powerful indicators of microstructural information in the brain. DKI has been successfully used to evaluate aging, attention deficit hyperactivity disorder, cerebral glioma, epilepsy, and head and neck cancer in vivo, and has been shown to capture diffusion and kurtosis alterations especially well in white matter 12,13 .…”
Section: Ivyspringmentioning
confidence: 99%